Capital Adequacy Ratio and Performance of Joint Stock Commercial Banks in Vietnam - Tran Ngoc Thy , Tho; Pham Le, Thong (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This paper scrutinizes the simultaneous relationship between capital adequacy ratio (CAR) and performance, measured by ROE, of joint stock commercial banks in Vietnam based on the simultaneous equation system of the two variables. The data in the analysis are collected from the financial statements and annual reports of 27 joint stock commercial banks in the period 2016–2022. Estimation results of the system of equations using 3SLS estimation together with fixed effects and time effects confirm a simultaneous and positive relationship between CAR and ROE, that is, an increase in ROE results in an increase in CAR and vice versa, an increase in CAR also causes an increase in ROE. During the COVID-19 outbreak, banks with high CAR ratios can enhance their financial capacity and stability, thereby creating confidence for investors and increasing the profitability. On the contrary, banks with high ROE may have better capital accumulation capabilities and maintain higher CAR ratios. The research results also show that commercial banks increase CAR over time but ROE decreases, especially during the COVID-19 outbreak in 2020–2022.